Influence of Age and Phylogenetic Background on Blood Parameters Associated With Bone Metabolism in Laying Hens - Habig, Christin; Weigend, Annett; Baulain, Ulrich; Petow, Stefanie; Weigend, Steffen (Frontiers in Physiology, 2021)
The high laying performance of today’s laying hens places enormous demands on their mineral metabolism. While up-to-date data are rare, the present study aimed to describe blood parameters associated with egg laying and bone metabolism during the pre-laying period, in the course of the laying period and the daily egg laying cycle. Ten to 15 laying hens of two high-performing, phylogenetically divergent lines (BLA: brown-egg layer; WLA: white-egg layer), kept in single cages were blood sampled at 17, 25, 29, 49 and 69 weeks of age. Sampling was made at 6 a.m., 10 a.m., 2 p.m. and, with the exception of week 17, 6 p.m. Blood samples were analyzed for concentrations of total and ionized calcium, anorganic phosphate (PO4), markers of bone formation (osteocalcin) and resorption (carboxyterminal crosslinked telopeptide of type I collagen (CTX-I)), 25-hydroxycholecalciferol (25(OH)D3) and estradiol-17β. In the pre-laying period (17 wk), the estradiol-17β level calculated for WLA was more than twice as high as the level calculated for BLA, while no significant difference could be observed in the laying period (25 to 69 wks). BLA hens had significantly higher total calcium concentrations at 49 weeks of age as well as up to twice as high levels of osteocalcin and 25(OH)D3 than WLA at any time of the day from 25 to 69 weeks of age. While osteocalcin, CTX-I and 25(OH)D3 concentrations were significantly higher before the onset of lay, total calcium and estradiol-17β levels significantly increased from 17 to 69 weeks of age. In contrast, PO4 values varied only slightly during the experimental period and ionized calcium was highest at 17 and 49 weeks of age and lowest around peak production (29 wk). In the course of the daily egg laying cycle blood concentrations clearly reflected the stage of egg formation. Our results provide up-to-date data of bone- and egg laying-associated blood parameters of two contemporary layer lines over the course of the pre- and egg-laying period and the daily egg laying cycle. Differences between brown- and white-egg layers raise questions, whether phylogenetic background determines their efficiency to cope with high calcium demands relating to egg production.